From many, one : Indians, peasants, borders, and education in Callista Mexico, 1924-1935 - Marak, Andrae M. (Andrae Micheal) (Latin American and Caribbean series, 2009)
Offers a look at the educational policies and practices of the presidency of Plutarco Elias Calles in post-revolutionary Mexico. This title examines the Calles government's attempts to centralise control over education in the US-Mexican borderlands region and to transform its rural and indigenous inhabitants into more 'mainstream' Mexicans.